SISTEM DETEKSI KERUSAKAN PERMUKAAN JALAN RAYA DENGAN METODE TEMPLATE MATCHING - Daru Cahyono, Setiyo (JURNAL AGRI-TEK, 2014)
The development of information technology is urgently needed in various fields, one of them is in the field of Public Works, especially highways. One application of information technology in the field of Public Works is the detection of road damage by utilizing the images on the surface of the highway system-based computer. Systems using Template Matching method can make the detection of road damage. Road surface damage characteristics can be used to determine the damaged data and normal data. Preprocessing, feature extraction and pattern recognition will be performed on the data. Pattern recognition is done by Template Matching.Systems using Template Matching approach produces the percentage of success in the detection of road surface damage by 60% by using the 10 templates, and by 75% by using the 20 templates. Thus, the system is considered to be quite good at detection.Keyword : Damage of Road, Computer Based, Templete Matching